The pharmacokinetic of silver diamine fluoride in healthy children with dental caries / Lim Siau Peng - Lim, Siau Peng (2021)
Silver diamine fluoride (SDF) is a medication used topically on carious tooth surfaces to arrest caries progression in both child and adult populations. This study aimed to determine the pharmacokinetic of SDF in 15 children who received SDF treatment. Urine samples were collected at baseline, and at first and second 24 hours after SDF treatment to determine silver and fluoride levels. Hair samples were collected at baseline, and at days 7, 14, 30, 60, 75, and 90 after SDF to assess silver levels. The median and interquartile range of urinary fluoride at baseline, first and second 24 hours after SDF were 498.33 (381) µg/24-hour, 574.92 (318.87) µg/24-hour, and 474.35 (324.21) µg/24- hour, respectively. The pairwise comparison results indicated that urinary fluoride levels at the first 24 hours after SDF treatment were significantly higher than those at the baseline. However, the higher urinary fluoride levels are not sufficient to cause fluorosis as SDF is not for daily application. The range of urinary silver levels at baseline, and the first and second 24 hours after SDF were <1 µg/24-hour, 1 – 2 µg/24-hour and <1 µg/24- hour, respectively. Although urinary silver levels were higher in the first 24 hours following SDF, statistical analysis was not possible due to their extremely low levels. The range of hair silver levels after SDF treatment (< 0.2-0.69 µg/g) were found to fluctuate around the baseline level (<0.2-1.7 µg/g). Based on these study results, the use of SDF is safe in children. Keywords: Silver diamine fluoride, caries teeth, children, pharmacokinetic, safety